Computer modelling and assessment methodology for the thermal energy performance analysis of institutional buildings in Nigeria - Adamu Bena, Aminu (2024)
Nigerian economic growth is spurred by the increasing population and the need for modern infrastructure. The energy and construction sectors are under immense pressure to meet the increasing demand for housing, educational, commercial, and health buildings and a reliable electrical power supply grid. In addition, to contribute to reducing the impact of climate change, the governmental authorities are required to develop clear and enforceable national construction codes and related building energy efficiency measures specific to the diverse climates of the country. However, there is currently little research on institutional educational building infrastructure, specifically targeting thermal comfort provision applicable to the diverse Nigerian climatic zones. This research explored ways of improving university buildings' thermal comfort and energy performance in the hot-dry town of Birnin Kebbi (latitude 12.45°S; longitude 04.20°N), Nigeria. The research investigated two University learning buildings with mix-mode ventilation, where overheating in the indoor space is prevalent. The research identified that high solar radiation exposure, inadequate orientation below standard construction materials, and inefficient building delivery were among the parameters that contributed to thermal discomfort to occupants. The research methodology involves both qualitative and quantitative evaluation of thermal comfort using computer modelling, which is a direct measurement of building space operating parameters of temperature and humidity and a survey of building occupants. Integrated Environmental Solutions Virtual Environment (IESVE) software was used as the main analytical tool for parametric and energy efficiency analysis. The subjective evaluation of occupants by interview and questionnaire administration through the Post Occupancy Evaluation (POE) process was carried out using ASHRAE-55 Standard guidelines to investigate and analyse the Predictive Mean Vote (PMV) and Percentage of People Dissatisfied (PPD) votes of the occupants concerning the comfort perceptions and level of satisfaction with indoor conditions across the seasons. The findings from the experimental measurement of collected data and POE investigations show that the building operates outside the recommended indoor temperature of 26°C for educational buildings. In effect, the lower and upper indoor temperatures were 27.0°C and 32.0°C, respectively, while the comfort temperature was of 29.5°C. The findings from simulations reveal that shading devices applied on the external fabric of the buildings could form an effective passive strategy for solar heat gain control, but this can compromise the daylighting level required for the learning environment. The computer simulation shows that by implementing passive design strategies (building orientation, insulation, shading), the cooling load of the studio and classroom areas of the building can be reduced by 32% and 28%, respectively. However, the simulated daylight factor (DLF) for the two spaces was 4.6% and 1.6%, respectively, indicating that the classroom complex was below the minimum light level standard. Furthermore, the research investigated the integration of renewable energy in the form of PV panels to generate low-carbon power to offset part of the cooling load of the building. The computer modelling shows that by integrating PV panels on the available roof area of the studio and classroom buildings, up to 127MWh and 213MWh of annual electrical power can be generated, respectively. Therefore, this study recommends that renewable energy resources by integrating PV panels to support a sustainable supply of energy to the buildings and the minimum shading standard achieved in the research should be incorporated in the Nigerian Building Code and Building Energy Efficiency document.